2016
DOI: 10.1016/j.bbi.2016.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of IL1B single nucleotide polymorphisms on depressive and anxiety symptoms are determined by severity and type of life stress

Abstract: Interleukin-1β is one of the main mediators in the cross-talk between the immune system and the central nervous system. Higher interleukin-1β levels are found in mood spectrum disorders, and the stress-induced expression rate of the interleukin-1β gene (IL1B) is altered by polymorphisms in the region. Therefore we examined the effects of rs16944 and rs1143643 single nucleotide polymorphisms (SNPs) within the IL1B gene on depressive and anxiety symptoms, as measured by the Brief Symptom Inventory, in a Hungaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
37
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 51 publications
2
37
0
1
Order By: Relevance
“…Central administration of IL-1β produces several stress-like effects and pathological changes [12, 1416]. Hippocampal tissue inflammation and, particularly, enhanced interleukin-1β (IL-1β) signaling may contribute to depression [17]. In contrast, blockade of the hippocampal IL-1β receptor, IL-1RI, abolishes the anhedonic behavioral effects of chronic unpredictable stress (CUS) [18, 19].…”
Section: Introductionmentioning
confidence: 99%
“…Central administration of IL-1β produces several stress-like effects and pathological changes [12, 1416]. Hippocampal tissue inflammation and, particularly, enhanced interleukin-1β (IL-1β) signaling may contribute to depression [17]. In contrast, blockade of the hippocampal IL-1β receptor, IL-1RI, abolishes the anhedonic behavioral effects of chronic unpredictable stress (CUS) [18, 19].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, various SNPs in genes coding for both IL-1β and IL-1R2 have been linked to increases in both state and trait anxiety [23]. IL-1β gene polymorphisms also affect an individual’s response to stress events to predispose individuals to anxiety and depression disorders [24] underscoring the importance of IL-1β to anxiety and mood disorders in humans. Given that fasting is known to reduce some of the sickness symptoms associated with the peripheral administration of IL-1β [25], we sought to show, that in the healthy state, fasting has a beneficial impact on anxiety, and this is mechanistically tied to inhibition of IL-1β priming and activation within the brain.…”
Section: Introductionmentioning
confidence: 99%
“…Disturbances in the genetic expression pro le of proinᴀammatory cytokines such as Interleukin-1B (IL-1B) and Interleukin-6 (IL-6) has been reported to inᴀuence these mood disorder pheontypes profoundly, however it has been also shown that different stressors are needed to exert such effect. That means that signi cant main effects of these genes on depression and anxiety are lacking, but highly signi cant interaction effects could be observed even after correcting for multiple testing [1,2] The aim of this study was to represent how the different stress clusters can interact with two IL-1B, and an IL-6 polymorphisms, inᴀuencing anxiety phenotype in a normal population sample from Hungary. For the analysis 1093 people were recruited, provided genetic samples and phenotypic information.…”
Section: Mta-se Neuropsychopharmacology and Neurochemistry Research Gmentioning
confidence: 99%
“…For the analysis 1093 people were recruited, provided genetic samples and phenotypic information. Linear regression analyses were carried out with PLINK (1,2) ( This study provides an example for the interplay among interaction patterns in the pathomechanism of anxiety symptoms. Among the examined stress types we found that IL-1B polymorphisms are more sensitive to early life stress than any other interaction we found.…”
Section: Mta-se Neuropsychopharmacology and Neurochemistry Research Gmentioning
confidence: 99%
See 1 more Smart Citation